PEMURNIAN CRUDE GLYCERINE MELALUI PROSES BLEACHING DENGAN MENGGUNAKAN KARBON AKTIF - M. Afif Aufari; Sia Robianto; Renita Manurung (Jurnal Teknik Kimia USU, 2013)
Crude glycerine is a concentrated liquid that with the glycerin content less than 88%. Crude glycerine has the dye produced by caroten. Caroten or usually called reddish yellow colour pigments cause the palm oil colour to be reddish yellow. Caroten is soluble in oil and fat but not in the water. Colours has a low quality and did not preferred by consumer and must be eliminated. This compound can be eliminated by a absorption process using activated carbon. The using of crude glycerine will further produce the product drugs and cosmetics industries. This research is conducted to study absorbtion of activated carbon to the crude glycerine impurities that causes the raddish yellow colour. This research do by using mesh, weight, and time of stirring with different variated.